Idiopathic Thrombosis of the Inferior Vena Cava and Bilateral Femoral Veins in an Otherwise Healthy Male Soldier - Sarah Gordon; Tamie Kerns; William Londeree; Brian Ching (Case Reports in Medicine)
Thrombosis of the inferior vena cava is less common than deep venous thrombosis of the lower extremities, particularly in the absence of an obvious congenital caval abnormality or hypercoagulable state. We present a case of IVC thrombosis in an otherwise healthy and active 28-year-old male soldier secondary to dehydration and venous webbing. IVC thrombosis is an uncommon and underrecognized condition; in this case, the patient’s caval thrombosis was initially mistaken for acute back strain. Prompt recognition is necessary to minimize long-term sequelae.